1990
DOI: 10.1177/073168449000900104
|View full text |Cite
|
Sign up to set email alerts
|

Delamination Resistance in Stitched and Unstitched Composite Plates Subjected to Impact Loading

Abstract: The delamination resistance of a composite plate subjected to low-velocity impact is dependent on the interlaminar strengths and the level of interlaminar stress. The former is strongly influenced by the material properties such as matrix toughness and fiber-matrix bonding strength while the latter can be affected by the specimen geometry and loading parameters. In this study, some thin composite plates were fabricated and sub jected to low-velocity impact. The delamination in every specimen was examined. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 6 publications
0
59
0
Order By: Relevance
“…Liu's findings [22] show that stitching enhances the interlaminar strength and diminishes the damage area. The delamination resistance was inspected with respect to the effectiveness of various stitch patterns and across a variety of stitch densities.…”
Section: The Effects Of Stitching On the Mechanical Properties Of Mulmentioning
confidence: 94%
See 1 more Smart Citation
“…Liu's findings [22] show that stitching enhances the interlaminar strength and diminishes the damage area. The delamination resistance was inspected with respect to the effectiveness of various stitch patterns and across a variety of stitch densities.…”
Section: The Effects Of Stitching On the Mechanical Properties Of Mulmentioning
confidence: 94%
“…The delamination resistance was inspected with respect to the effectiveness of various stitch patterns and across a variety of stitch densities. Liu pointed out [22] that stitching impedes the propagation of delamination and reduces the delamination area in accordance with the increase of stitch density.…”
Section: The Effects Of Stitching On the Mechanical Properties Of Mulmentioning
confidence: 99%
“…The use of thermoplastic and toughened thermoset matrices is one possibility [9][10][11]. However, it has been observed that through-thickness reinforcement is the most effective way to suppress delamination [12][13][14][15][16][17][18][19]. The simplest way to achieve through-thickness reinforcement is by means of transverse stitching.…”
Section: Introductionmentioning
confidence: 99%
“…Methods of reducing interply delamination include the use of tougher matrix systems, woven fabrics, and through-thickness reinforcement. The main methods of through-thickness reinforcement include 3-D weaving, pinning, and stitching, of which stitching has been demonstrated to be most effective in improving the delamination resistance [14][15][16][17][18][19][20][21][22][23][24][25]. The early attempts of improving delamination resistance were made by Huang et al [14] in the late 1970s where steel wires of 0.33 mm diameter were placed at ±45° angles to the thickness of the laminate separated by 1.6 mm.…”
Section: Introductionmentioning
confidence: 99%